Cytochrome P450‐mediated interaction between perazine and risperidone: implications for antipsychotic polypharmacy. (2nd March 2017) - Paulzen, Michael; Haen, Ekkehard; Hiemke, Christoph; Stegmann, Benedikt; Lammertz, Sarah E.; Gründer, Gerhard; Schoretsanitis, Georgios
Abstract : Background: Although clinically widespread, scientific evidence for antipsychotic polypharmacy is still limited. Combining different drugs increases the potential for drug–drug interactions, enhancing the risk of adverse drug reactions. We aimed to unravel the potential pharmacokinetic interactions between risperidone (RIS) and perazine. Methods: Using a therapeutic drug monitoring database containing plasma concentrations of RIS and its active metabolite [9‐hydroxyrisperidone (9‐OH‐RIS)], we considered two groups: a group of patients under antipsychotic monotherapy with RIS ( n  = 40) and a group of patients that was comedicated with perazine ( n  = 16). Groups were matched for demographic characteristics and daily dosage of RIS. Plasma concentrations, concentrations corrected for the dose (C/D) of RIS, 9‐OH‐RIS and the active moiety (RIS + 9‐OH‐RIS), as well as the metabolic ratios of concentrations of 9‐OH‐RIS/RIS, were compared using nonparametric tests. Results: All parameters other than plasma concentrations and the C/D ratio of 9‐OH‐RIS differed between groups. Median values for plasma concentrations of the active moiety and C/D of the active moiety were higher in the perazine group ( P  < 0.001 and P  < 0.001, respectively). Differences were driven by variations in the plasma concentrations and C/D of RIS, which were higher in the perazine group ( P  < 0.001 and P  < 0.001, respectively). Metabolic ratios were lower in the perazine group ( P  = 0.003). Discussion: The coadministration of perazine in RIS‐medicated patients leads to significantly higher plasma concentrations and C/D values of RIS and its active moiety, and a lower metabolic ratio, reflecting the cytochrome P450 (CYP) 2D6 phenotype. We suggest that the mechanism underlying the effect of perazine on RIS metabolism is based on an inhibition of CYP2D6 and CYP3A4 activity.